The Effectiveness of a Positive Parenting Program on the Relationship between Mothers and Children with Autism Spectrum Disorder - Saeid Hassanzadeh; Ali Masah Bavani (پژوهش‌های کاربردی روانشناختی, 2021)
. The attempt to reduce clinical problems in children with autism through parenting has been taken up by researchers in recent years. The purpose of this study is to evaluate the effectiveness of a positive parenting program on the relationship between mothers and children with autism spectrum disorder. The present study is a quasi-experimental study with a pretest-posttest design and a control group. The statistical population includes all mothers of children aged 7 to 12 years with autism spectrum disorder in Isfahan, from which 30 individuals were randomly selected and divided into two groups of experimental and control groups each with 15 individuals. The experimental group attended 8 sessions of the positive education program (one session per week and 90 minutes per session), while no training was provided for the control group. The instrument used in this study was the Pianta Parent-Child Relationship Scale (CPRS). Data were analyzed using multivariate analysis of covariance with SPSS software (version 26). The results showed a significant difference between pre-test and post-test scores (p <0.05). It can be concluded that positive parenting program improves the relationship between mother and child with autism spectrum disorder, and can be used to reduce the negative behaviors of children with autism spectrum disorders.